1977
DOI: 10.1002/art.1780200808
|View full text |Cite
|
Sign up to set email alerts
|

Localization of C‐reactive protein in synovium of patients with rheumatoid arthritis

Abstract: Synovial biopsies from 8 patients with rheumatoid arthritis, 2 patients with degenerative osteoarthritis, and 4 patients with nonarthritic disease were studied for localization of C-reactive protein (CRP) using immunofluorescence microscopy. The nuclei of many synoviocytes and histiocytes in rheumatoid synovial membrane were found to bind CRP. Cultures of rheumatoid synovium in 14C-labeled amino acids produced radioactive IgG, IgM, IgA, and C3, but not CRP, indicating the synovial-bound CRP was not of local or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Copper is a cofactor for several major cartilage enzymes but the mechanisms involved in intracellular copper transport in chondrocyte s are unknown. Recent studies have revealed that many cells and tissues express transcripts of ceruloplasminlike proteins, including human neonatal cartilage, human fetal chondrocytes, chondrosarcom a cells (19), synovial cells (20). A cartilage matrix glycoprotein (GMGP) (21), a disul® de bounded 550kDa protein, which possesses an amino acid sequence homology with ceruloplasmin, synthesized by chondrocytes , was demonstrated to bind copper and have some oxidase activity similar to that of ceruloplasmin (22) and might serve as a copper transport protein in chondrocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Copper is a cofactor for several major cartilage enzymes but the mechanisms involved in intracellular copper transport in chondrocyte s are unknown. Recent studies have revealed that many cells and tissues express transcripts of ceruloplasminlike proteins, including human neonatal cartilage, human fetal chondrocytes, chondrosarcom a cells (19), synovial cells (20). A cartilage matrix glycoprotein (GMGP) (21), a disul® de bounded 550kDa protein, which possesses an amino acid sequence homology with ceruloplasmin, synthesized by chondrocytes , was demonstrated to bind copper and have some oxidase activity similar to that of ceruloplasmin (22) and might serve as a copper transport protein in chondrocytes .…”
Section: Discussionmentioning
confidence: 99%
“…CRP binds histones [74], small nuclear ribonucleoproteins [7] and ribonucleoprotein particles [75]. In keeping to this, CRP deposition is known to be abundant in proximity of the nuclei of necrotic cells in humans affected by chronic inflammatory diseases such as rheumatoid arthritis [76]. Finally, CRP has been reported to exert a certain tumoricidal activity [77] and protect mice against cellular toxicity following the exposition to bacterial lipopolysaccharide [78].…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…7477 The interaction is Ca 2+ -dependent and involves the PCh-binding site of CRP. 75–77 CRP, however, does not bind chromatin in serum suggesting that this interaction occurs only if CRP or chromatin is deposited at sites of inflammation.…”
Section: Short Pentraxins: Crp and Sapmentioning
confidence: 99%